2016
DOI: 10.1063/1.4964619
|View full text |Cite
|
Sign up to set email alerts
|

A new kind of spoof surface plasmon polaritons structure with periodic loading of T-shape grooves

Abstract: A new kind of spoof surface plasmon polaritons (SSPPs) structure with periodic loading of T-shape grooves is introduced in this paper. Dispersion property of this proposed structure is investigated in detail, and comparisons of dispersion property of the proposed structure and that of the traditional SSPPs structures, including structure with rectangular grooves and structure with trapezoidal grooves, are also made. The SSPPs field confinement along the orthogonal directions of the proposed structure is studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Surface plasmon resonance [1] in patterned metals has triggered a number of exciting applications [2][3][4][5][6][7][8][9], due to its ability to push the conventional boundary of resolution beyond the Abbe diffraction limit [10]. However, surface plasmon has also got its own limitations as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface plasmon resonance [1] in patterned metals has triggered a number of exciting applications [2][3][4][5][6][7][8][9], due to its ability to push the conventional boundary of resolution beyond the Abbe diffraction limit [10]. However, surface plasmon has also got its own limitations as well.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the argument of conservation of field polarization, it was hypothesized that [15], even in thin structures, the main characteristics of SSPP metamaterial with infinite thickness are retained, and hence the standard theory for spoof plasmon [9,[21][22][23][24], originally derived for 3D structure, requires no revision. Because of the apparent resemblance between the dispersion behaviour of a 3D SSPP structure and that of its 2D planar counterpart, it was deemed redundant to perform an exclusive analysis of the planar SSPP structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have demonstrated the higher propagation confinement and low-loss features associated with T-shaped grooves when compared to rectangular, V, dumbbell and trapezoidal grooves etched on conventional SPP TLs [32,33]. In this paper, we exploit these unique features associated with T-shaped grooves when forming a band-rejection filter for the first time when we consider their interaction with SSPP TLs.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the mechanism of SSPPs, a microwave bandpass filter (BPF) is realized in [14] by employing a periodic subwavelength metallic Domino array. A new kind of SSPP structure with periodic loading of T‐shape grooves is introduced in [15]. A comb‐shaped SSPP structure loaded with two H‐shaped cells in the centre forms a non‐periodic SSPP [16], and a highly selective wideband bandpass filter (BPF) is realized by using spiral‐shaped defected ground structure on coplanar waveguide (CPW).…”
Section: Introductionmentioning
confidence: 99%